(untitled) (Al-Aasar, 2025)
Translation is not only a laborious work, but is also very sensitive, because translation cannot be better than the original work nor inferior. It is essential for a translator to convey the actual message, while translating, not the words. In this way, translation consist of two brains, one is the creator of the idea and the second one is of the translator. A translator should avoid all prejudices and pressures, otherwise the translation will be considered a treachery and the translator will be called a traitor. And this translationship is more piousness and dangerous than the state rebellion. It impacts on all the people of the world, who understand it, and also passes on to other people. This is the message which is not of the creator, but has been assigned to his name.